PENGARUH KUALITAS MEMBACA TERHADAP PRESTASI AKADEMIK MAHASISWA - Jurnal Ekonomi (Journal of Economic Education and Entrepreneurship, 2026)
Technological developments have brought about a new phenomenon among students and pupils in accessing information, from the habit of reading text to audio-visual information. This study aims to determine: the quality of reading and its influence on the academic achievement of students of Economics Education at Ivet University Semarang. The research approach was quantitative, with a population of 103 students and a sample of 79 students. The research variables consisted of reading quality (X) as the independent variable, which was measured through five indicators, namely: reading speed, content comprehension, ability to connect reading with knowledge, reading habits, and vocabulary mastery, as well as academic achievement (Y) as the dependent variable. Data collection techniques used questionnaires, documentation, and interviews. Simple regression inferential statistical techniques were used for data analysis and hypothesis testing. The results of the study showed: the average quality of students' reading was in the sufficient category; the average academic achievement was 3.65 in the very satisfactory category and the regression coefficient t count 3.148 > t table 1.664 at a significance of 0.002 < 0.05, with the conclusion that reading quality had a positive and significant effect on academic achievement, with a determination coefficient value of 11.4%, which indicates the contribution of reading quality to students' academic achievement.